Pursuing pleasance: Interrogating energy-intensive visions for the smart home. Issue 136 (April 2020) - Strengers, Yolande; Hazas, Mike; Nicholls, Larissa; Kjeldskov, Jesper; Skov, Mikael B.
Highlights: Qualitative content analysis of online, magazine and trade articles about the 21st Century smart home. Identifies energy-intensive vision of 'pleasance' and its seven qualities. Shows how plesance may undermine energy savings from smart devices (thermostats and lighting). Suggests alternative low-energy visions for designing the desirable smart home. Abstract: In recent years, household sustainability has received increasing attention in the field of Human-Computer Interaction. This has largely been driven by the argument that through interaction design, we can create 'smart homes' that enable households to be more responsible with precious resources, such as food, water and energy. However, the assumption that home automation technologies lead to improved sustainability may not hold. As a contribution to this discussion, this paper demonstrates how home automation devices promote a lifestyle vision which may undermine intended energy savings. Drawing on a qualitative content analysis of smart home articles, we identify and interrogate the industry vision of 'pleasance'. We highlight seven qualities that underpin this vision: aesthetic experience, fun and cool, customisation and control, convenience and simplicity, peace of mind, extension and expansion, and effortless energy-saving. We analyse how energy-intensive pleasance is embedded within two commercially available types of devices: smart thermostats and networked lighting. We show how these devices and the pleasance vision that they mobilize may encourage householders to use more energy. The paper concludes with design suggestions on how HCI community can re-envision pleasance through the examples of thermostats and networked lighting to achieve energy reductions and sustainability outcomes.